Revealing Indonesia through The Grief of Film: Marlina The Murderer in Four Acts - Fitriansal Fitriansal (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study is based on qualitative research using the grief of film model in the five stages of Kubler-Ross. The aim is to unveil the grief of the film "Marlina The Murderer in Four Acts" by Mouly Surya, constructed through the exotic cultural anthropology of Indonesia, inspired by a true story in the Sumba region. The research results indicate that the film depicts the character Marlina undergoing a grief process in constructing its narrative. The film's foundation lies in the truth of reality, interpreted through Indonesia's ideology, utilizing the grand power of art and culture. This ultimately gives rise to the concept of the essence of interpreting nationalism through the character 'Marlina' as a representation of marginalized women challenging the nation's reality.